Case Report: Multiple Causes of Cardiac Death After the First Infusion of Atezolizumab: Histopathological and Immunohistochemical Findings - Kushnareva, Ekaterina; Stepanova, Maria; Artemeva, Elizaveta; Shuginova, Tatyana; Kushnarev, Vladimir; Simakova, Maria; Moiseenko, Fedor; Moiseeva, Olga (Frontiers in Immunology, 2022)
Immune checkpoint inhibitors are promising agents for anticancer therapy. But despite their high efficacy in the treatment of solid tumors there is still a problem with immune related adverse events especially cardiovascular complications with very high mortality rate. Myocarditis or ischemic heart disease progression are not the only possible causes of cardiovascular death in patients treated by checkpoint inhibitors. We report a case of a patient with mucinous carcinoma of the lung, with a previous history of hypertension and moderate left ventricular dysfunction. The patient was prescribed with atezolizumab, but the first atezolizumab infusion resulted in the patient cardiovascular death. Post-mortem histopathological evaluation of myocardium revealed several possible reasons for hemodynamic instability: tumor embolism of the coronary arteries, micrometastases of mucinous carcinoma in myocardium, and myocarditis diagnosed by both Dallas and immunohistochemistry criteria. In addition, testing for expression of PD-L1 detected the high levels of membranous and cytoplasmic PD-L1 protein even in the myocardium area free from tumor cells. The present clinical case demonstrates a problem of cardiovascular death in patients treated with checkpoint inhibitors and actualizes the need for future research of potential risk factors for cardiovascular complications.